2020
DOI: 10.1093/geroni/igaa013
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Landscape of Imagining Life Beyond the Current Life Span: Implications for Construal and Self-Continuity

Abstract: Background and Objectives With rapid advancements in medicine, technology, and nutrition, the future holds the possibility of longer and healthier lives. Despite garnering attention from myriad disciplines, psychological perspectives on life extension are scarce. In three studies, we addressed this gap by exploring key mental characteristics and psychological variables associated with simulating an expanded life span and thus an extremely distant future self. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Although it has been shown that cognitive impairments are associated with alterations in specific brain regions (Liang & Carlson, 2020; Reas et al., 2018; Roldán‐Tapia et al., 2012), a detailed knowledge of the ultrastructural changes in such areas is lacking. Numerous studies have evaluated brain processing of cognitive functions including memory speed, decision‐making, attention, and perception during aging using functional magnetic resonance imaging (Branch et al., 2019; Löckenhoff & Rutt, 2017; Löckenhoff et al., 2020; Tausen et al., 2020). These and other morphological studies indicate structural modifications such as decrease of synapse and spine densities, decrease in grey matter and volume as well as microcolumn disorganization in cognitive regions of the brain (Alexander et al., 2020; Bonifazi et al., 2018; Guerra‐Gomes et al., 2018; Peters & Kemper, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been shown that cognitive impairments are associated with alterations in specific brain regions (Liang & Carlson, 2020; Reas et al., 2018; Roldán‐Tapia et al., 2012), a detailed knowledge of the ultrastructural changes in such areas is lacking. Numerous studies have evaluated brain processing of cognitive functions including memory speed, decision‐making, attention, and perception during aging using functional magnetic resonance imaging (Branch et al., 2019; Löckenhoff & Rutt, 2017; Löckenhoff et al., 2020; Tausen et al., 2020). These and other morphological studies indicate structural modifications such as decrease of synapse and spine densities, decrease in grey matter and volume as well as microcolumn disorganization in cognitive regions of the brain (Alexander et al., 2020; Bonifazi et al., 2018; Guerra‐Gomes et al., 2018; Peters & Kemper, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The prospect of life extension brings forth new questions regarding how humans will psychologically react to the possibility of increased lifespans. In one exception, researchers found that participants were able to imagine expanded lifespans, but reported lower self-continuity and connection to their future selves (Tausen et al., 2020), suggesting there are likely psychological complexities regarding one’s sense of self, as well as practical barriers (such as saving for extended retirement or maintaining adequate physical health) to actually participating in life extension technologies at the present time.…”
Section: Introductionmentioning
confidence: 99%